The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1590/s0100-69162009000300011
|View full text |Cite
|
Sign up to set email alerts
|

Imagens de sensoriamento remoto no monitoramento da colheita da cana-de-açúcar

Abstract: RESUMO:A prática agrícola da queima da palha da cana-de-açúcar tem por finalidade facilitar a colheita manual. No Estado de São Paulo, essa prática está submetida a uma rigorosa legislação ambiental devido ao impacto negativo para o meio ambiente. Está previsto que a queima da cana deve ser gradativamente eliminada até 2017. O presente trabalho tem por objetivo avaliar a área de cana colhida com e sem queima em todo o Estado de São Paulo. Para tal, foram utilizadas as imagens disponíveis do sensor TM a bordo d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
10

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 11 publications
(10 reference statements)
0
9
0
10
Order By: Relevance
“…However, Aguiar et al [6] reported, also for the state of Sã o Paulo, that during the 2006 season 3.24 million ha were harvested and that 33.5% (1.09 million ha) were harvested without straw burning and 66.5% (2.15 million ha) with straw burning. Comparing the results it can be concluded that from 2006 to 2008 the unburned harvested area increased by 0.84 million ha and the burned area decreased by 0.15 million ha.…”
Section: Harvest Monitoringmentioning
confidence: 99%
“…However, Aguiar et al [6] reported, also for the state of Sã o Paulo, that during the 2006 season 3.24 million ha were harvested and that 33.5% (1.09 million ha) were harvested without straw burning and 66.5% (2.15 million ha) with straw burning. Comparing the results it can be concluded that from 2006 to 2008 the unburned harvested area increased by 0.84 million ha and the burned area decreased by 0.15 million ha.…”
Section: Harvest Monitoringmentioning
confidence: 99%
“…Embora pesquisas (AGUIAR et al, 2009;MERCANTE et al, 2009;JOHANN et al, 2012;RISSO et al, 2012;MERCANTE et al, 2012;JUNGES et al, 2013) tenham obtido relativo êxito na utilização de sensores remotos orbital para o monitoramento da atividade agrícola, o principal desafio está em desenvolver uma metodologia sistemática sincronizada com as necessidades do mercado.…”
Section: Introductionunclassified
“…Based on these maps, sugarcane harvest can be monitored with the use of remote sensing images which identify the type of harvest: green harvest (GH) or pre-harvest burning (BH) [6,9]. Partial results on the remote sensing harvest monitoring were published by Aguiar et al [10] and Rudorff et al [6] for crop years 2006/07 and 2008/09, respectively. The objective of the present work is to analyze a series of five years of continuous sugarcane harvest monitoring, based on remote sensing images, to evaluate the effectiveness of the "Green Ethanol" Protocol in anticipating the end of the sugarcane burning practice in São Paulo State.…”
Section: Introductionmentioning
confidence: 99%